Morphological sexual maturity of the marine crab Xanthodius parvulus at the State Marine Park Laje de Santos, São Paulo, Brazil - Chellegatti, Isabela [UNESP]; da Costa, Rogério Caetano [UNESP]; Castilho, Antonio L. [UNESP]; Moraes, Isabela R. R. [UNESP]; Herrera, Daphine R. [UNESP]; Davanso, Thiago M. (FapUNIFESP (SciELO), 2021)
The marine crab Xanthodius parvulus (Fabricius, 1793) is naturally distributed in the Western Atlantic, being commonly found in the northeastern Brazilian coast. However, this species has been also recorded in the southeastern coast, especially in São Paulo State, on islands located close to harbors, which are becoming a place of occurrence for exotic species. This study aimed to estimate the morphological sexual maturity (relative growth) of X. parvulus the functional biological patterns of the species in a No-take marine reserve. The crabs were sampled at the Marine State Park of Laje de Santos, an important protected area from São Paulo that is located close to the largest Brazilian harbor, Santos, using an artificial substrate and active search methods (scuba diving). The morphological sexual maturity of females was estimated in 7.28 mm, according to the Abdomen Width vs. Carapace Width relationship, while for males this value was 8.83 mm based on the Gonopod Length vs. Carapace Width relationship, the females presented an increase in abdominal growth, even during the mature stage in order to achieve higher reproductive success, since the abdominal structure is used to protect the embryos. The Gonopod Length vs. Carapace Width relationship showed that males copulate with different sized females, since a non-exaggerated growth of the gonopods keeps them adequate to the size of the female genital pore, i.e., juveniles exhibited negative allometry and adults presented isometry. Thus, estimating the size of the sexual maturity of a species requires the development of a model to acknowledge its biological and reproductive pattern, being an important tool to increase the knowledge about the behavior of this species and one of the parameters to evaluate its conservation status.
Maturidade sexual morfológica do caranguejo marinho Xanthodius parvulus no Parque Estadual Marinho Laje de Santos, São Paulo, Brasil
Keywords: Brachyura; Continental Islands; Growth; Relative growth; Reproduction